ClinLabGeneticist: a tool for clinical management of genetic variants from whole exome sequencing in clinical genetic laboratories. Issue 1 (December 2015) - Wang, Jinlian; Liao, Jun; Zhang, Jinglan; Cheng, Wei-Yi; Hakenberg, Jörg; Ma, Meng; Webb, Bryn; Ramasamudram-chakravarthi, Rajasekar; Karger, Lisa; Mehta, Lakshmi; Kornreich, Ruth; Diaz, George; et al.
Abstract Routine clinical application of whole exome sequencing remains challenging due to difficulties in variant interpretation, large dataset management, and workflow integration. We describe a tool named ClinLabGeneticist to implement a workflow in clinical laboratories for management of variant assessment in genetic testing and disease diagnosis. We established an extensive variant annotation data source for the identification of pathogenic variants. A dashboard was deployed to aid a multi-step, hierarchical review process leading to final clinical decisions on genetic variant assessment. In addition, a central database was built to archive all of the genetic testing data, notes, and comments throughout the review process, variant validation data by Sanger sequencing as well as the final clinical reports for future reference. The entire workflow including data entry, distribution of work assignments, variant evaluation and review, selection of variants for validation, report generation, and communications between various personnel is integrated into a single data management platform. Three case studies are presented to illustrate the utility of ClinLabGeneticist. ClinLabGeneticist is freely available to academia athttp://rongchenlab.org/software/clinlabgeneticist .